2021
DOI: 10.1002/fsn3.2221
|View full text |Cite
|
Sign up to set email alerts
|

The low‐field NMR studies the change in cellular water in tilapia fillet tissue during different drying conditions

Abstract: Tilapia has the advantages of hypoxia tolerance, disease resistance capacity, rapid growth, and reproduction, and its nutritional value is high (Wang et al., 2019). In recent years, China became the top producers in the world to cultivate tilapia (FAO, 2017). In addition, in global fish farming, tilapia is the most popular farmed fish (Duan et al., 2011). But tilapia has high water content, and tilapia is apt to be highly spoilage when it is affected by enzymes and microorganisms (Kituu et al., 2010;Li et al.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Moreover, compared with bound water and non-flowing water, free water has the highest content. This is consistent with the findings of Luo et al (2021), which are attributed to cell membrane rupture. These results suggested that maternal high-dose vitamin D 3 addition could inhabit water mobility, increase juiciness, and improve the quality of pork batters in offspring pigs during cold storage period.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, compared with bound water and non-flowing water, free water has the highest content. This is consistent with the findings of Luo et al (2021), which are attributed to cell membrane rupture. These results suggested that maternal high-dose vitamin D 3 addition could inhabit water mobility, increase juiciness, and improve the quality of pork batters in offspring pigs during cold storage period.…”
Section: Discussionsupporting
confidence: 93%
“…Three peaks, T 21 (0.01–10 ms), T 22 (10–200 ms), and T 23 (>200 ms) were observed in Figure 2b and Table 2, corresponding to strongly bound water, partially immobilized water, and free water in the gel, respectively. The relative content of each water was represented by the graph's peak area (Luo, Li, Zhang, Zheng, & Ming Ling, 2021). T 2 reflects the combination degree of each water, and lower T 2 indicates a higher water‐binding degree (Li et al, 2012; Luo et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…These three forms represent: water closely bound with macromolecules, that is, binding water T 2b (0.1–1.0 ms); water inside the myofibril, that is, water that cannot easily flow T 21 (30–200 ms); and water outside the myofibril network, that is, free water T 22 (300–800 ms) (Bertram et al., 2002 ). The area of each peak, enclosed by the abscissa, is the water content of each part (Luo et al., 2021 ). Thus, the corresponding water content can be obtained by integrating each peak.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 outside the myofibril network, that is, free water T 22 (300-800 ms) (Bertram et al, 2002). The area of each peak, enclosed by the abscissa, is the water content of each part (Luo et al, 2021). Thus, the corresponding water content can be obtained by integrating each peak.…”
Section: Effects Of Different Water-retaining Agents On the Moisture ...mentioning
confidence: 99%